Cervical Lymph Node Metastasis From Recurrent Glioblastoma Detected by MRI and 2-[18F]FDG PET/CT. (14th March 2023) - Suárez-Piñera, Marina; Pudis, Michal; Vilariño, Noelia; Baixeras, Nuria; Torró, Carlos Majós
Abstract: A 53-year-old man diagnosed with recurrent glioblastoma after multimodal treatment on a follow-up brain MRI. Because of a palpable mass in the neck, the patient underwent a whole-body 2-[ 18 F]FDG PET/CT, which revealed hypermetabolic laterocervical confluent lymphadenopathies. A nodal cervical biopsy indicated distant metastases from glioblastoma. Recent studies have confirmed dural meningeal lymphatics, as part of the glymphatic system, which provide clearance of interstitial solutes from the brain parenchyma into cervical lymphatics. Nodal cervical metastases from glioblastoma, using this pathway, are extremely rare and have been almost unthinkable some years ago.